Understanding Hypertension during Pregnancy: Risk Factors and Prevention Strategies - Sholihatin, Illiyani; Murniati, Rinesita; Alami, Fathimah Nur; Aziri, Zirly Vera (Jurnal Biologi Tropis, 2024)
Hypertension during pregnancy is a major contributor to morbidity, mortality, and hospitalization for both mothers and their unborn infants. Hypertension during pregnancy can significantly raising the risk of chronic diseases in the mother including heart failure, stroke, and chronic kidney disease, as well as increasing the chance of preterm birth and low birth weight of the baby. This conditions includes chronic hypertension, gestational hypertension preeclampsia, and eclampsia. This paper aims to review existing literature about factors influencing hypertension in pregnancy and the strategies to prevent this conditions. The analyzed literature shows that the high prevalence of hypertension during pregnancy is associated with several risk factors, including body mass index (BMI), maternal age, multiple pregnancies, gestational diabetes, history of hypertensive disorders in prior pregnancies, type 2 DM, and a family history of conditions such as type 2 DM, hypertension, and preeclampsia. Additionally, other factors such as level of education and socioeconomic status also effect the incidence of hypertension in pregnancy. The data were collected through an online search of library databases such as ProQuest, PubMed, MDPI, ScienceDirect, and Google Scholar. This paper presents an overview of the risk factors and preventive strategies for hypertension during pregnancy.